English exposed : common mistakes made by Chinese speakers - Hart, Steve (Academic proofreader) (Hong Kong University Press, 2017)
Having analyzed the most common English errors made in more than 600 academic papers written by Chinese undergraduates, postgraduates, and researchers, Steve Hart has written an essential, practical guide specifically for the native Chinese speaker on how to write good academic English. English Exposed: Common Mistakes Made by Chinese Speakers is divided into three main sections. The first section examines errors made with verbs, nouns, prepositions, and other grammatical classes of words. The second section focuses on problems of word choice. In addition to helping the reader find the right word, it provides instruction for selecting the right style too. The third section covers a variety of other areas essential for the academic writer, such as using punctuation, adding appropriate references, referring to tables and figures, and selecting among various English date and time phrases. Using English Exposed will allow a writer to produce material where content and ideas--not language mistakes--speak the loudest.